Participation in higher education: A geodemographic perspective on the potential for further expansion in student numbers - Peter Batey; Peter Brown (European Regional Science Association (ERSA), 1998)
Higher Education in England has expanded dramatically in the last ten years with the result that currently more than 30 per cent of young people go on to University. This upward trend in the participation rate is almost certain to continue, following the recommendations of a national committee of inquiry, the Dearing Committee (National Committee of Inquiry into Higher Education 1997). Participation rates vary substantially by region and by type of residential area, and an earlier paper by the present authors (Batey, Brown and Corver 1997) demonstrated the benefits of using a geodemographic classification system to explore the nature of this variation. The present paper builds on this foundation in order to examine the potential for further expansion of student numbers. A number of scenarios are developed which combine assumptions about factors that may determine the scope for expansion in particular regions and sub-regions. The results of this analysis are intended to inform current discussions about the implementation of certain of the Dearing Committee?s recommendations. References Batey, P.W.J., Brown, P.J.B. and Corver, M. (1997) ?Expanding Participation in Higher Education: A Geodemographic Analysis of Recent Experiences in the English Regions? paper presented at the 27th European Congress of the Regional Science Association International, Rome, Italy 16-29 August 1997. National Committee of Inquiry into Higher Education, (1997), Higher Education in the Learning Society, London, HMSO.
Keywords: 330